Fatigue and dynamic aging behavior of a high strength Al-5024 alloy fabricated by laser powder bed fusion additive manufacturing. (November 2021) - He, Peidong; Webster, Richard F.; Yakubov, Vladislav; Kong, Hui; Yang, Qin; Huang, Shuke; Ferry, Michael; Kruzic, Jamie J.; Li, Xiaopeng
Abstract: A high strength Al-5024 alloy containing Sc and Zr with a bi-modal microstructure consisting of fine equiaxed and coarse columnar grains was successfully fabricated by laser powder bed fusion (LPBF) additive manufacturing. The formation of the bi-modal microstructure was mainly due to both the formation of primary Al3 Sc precipitates that act as nucleation sites and the steep temperature gradient during LPBF. By simulating the thermal field of a single melt pool, the formation mechanism of the bi-modal microstructure was explained. It was found by simulation that a solidification interface velocity less than 110 mm/s was beneficial to the nucleation of Al3 Sc precipitates and, hence, facilitated the formation of a fine grain microstructure. Applying different heat treatments revealed a trade-off trend between yield strength and ductility as a function of the heat treatment time, and a correlation in fatigue life and yield strength was observed, both of which were closely related to the status of the secondary Al3 Sc precipitates. The highest ultimate tensile strength of 450 MPa and corresponding 10 7 cycle fatigue strength of 105 MPa were achieved after hot isostatic pressing for 4 h at 325 °C with 100 MPa pressure. Dynamic strain aging was found to occur in both as-built and some heat treated samples, which was related to magnesium (Mg) solute atom clustering attributed to: (i) the formation of a diffuse "Mg wall" due to the repetitive melting and rapid cooling in LPBF, and (ii) the growth of intragranular (Al3 Sc) and intergranular precipitates (Fe-, Mn-rich) during subsequent heat treatment, thereby leading to an increasing number of misfit dislocations that promote the formation of Mg atom clusters. Graphical abstract: Image, graphical abstract